Ukraine : Technical Assistance Report-Strengthening Public Financial Management. (IMF Staff Country Reports; Country Report ;, 2019)
This Technical Assistance report on Ukraine discusses a more sustainable fiscal consolidation. The Ukrainian authorities have recently adopted a broad Public Financial Management System Reform Strategy, paving the way to decisive action in critical areas including medium-term budgeting, analysis and management of fiscal risks, and public investment management. Fiscal policy in Ukraine has been hampered by the lack of a medium-term orientation for the State Budget. Medium-term macroeconomic forecasts are regularly produced, but these are not well integrated with budget planning, which remains mostly incremental and annual in scope. Recent reform initiatives have prioritized the development of a medium-term budget framework to the forefront of the reform agenda; however, additional steps are required for it to be fully implemented. Ukraine has undertaken a range of reforms in public investment management, designed to tackle some of its weaker institutions. Nevertheless, the strategic planning process remains unfit for purpose and does not facilitate prioritization of capital investment projects.